Analisis Keuntungan Usaha Nasi Kuning “Ibu Jensy” Di Kelurahan Bahu Kecamatan Malalayang Kota Manado - Ricky Vincensius Dolang; Noortje M. Benu; Audrey J. M. Maweikere (AGRI-SOSIOEKONOMI, 2022)
This research aims to find out how much profit is earned by “Ibu Jensy” yellow rice business in Bahu Sub-District, Malalayang District, Manado City. This research was conducted from October to November 2021. The data collection in this study used interviews and documentation. The interview was conducted by directly interviewing the Nasi Kuning business owner as a respondent using a list of questions that had been prepared previously (questionnaire). Documentation is done by collecting data related to research both from relevant agencies and the internet. The data collected in this study were then analyzed using profit analysis using the Revenue Cost Ratio (R/C) analysis formula. Based on the research conducted, the results obtained that the yellow rice business "Ibu Jensy" in Bahu Sub-District, Malalayang District, Manado City is profitable because the total revenue is Rp. 610,000 per day, the total cost is Rp.441,614, so the profit obtained is Rp. 168,386 per day and get an R/C value of 1.38.